A Systematic Literature Review on Graduates’ Social Intelligence - Khairuddin, Muhammad Nadzrin; Mohamed, Mimi Nahariah Azwani (Journal of Techno-Social, 2023)
Social intelligence is becoming more important in the workplace as it helps people to be aware of their interactions which creates a harmonious working environment. As such, human resource officers are starting to prioritise this element as one of the criteria that they seek in a candidate during an interview. This paper is a systematic literature review on the current criteria that human resource officers look for during job interviews and their perceptions of graduates’ values in relation to social intelligence. This systematic literature review employed the four procedures by Gessler & Siemmer (2020) to clearly review previous literature. The review has highlighted that human resource officers have shifted their emphasis from academic performance to social intelligence when interviewing candidates during a job interview. However, graduates seem to have difficulties in showcasing social intelligence. Thus, further investigation is required in relation to how graduates perceive social intelligence and how they demonstrate social intelligence, either in oral or written communication. Apart from that, the review has also highlighted the inconsistencies in requirements between private and public sectors, as well as the size of the company. Thus, further investigation is needed to investigate these inconsistencies.